2013
DOI: 10.1007/s10147-013-0584-z
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance biopsy and active treatment during active surveillance for low-risk prostate cancer

Abstract: Surveillance biopsy is important for identifying patients who require active treatment. The results in this study allowed determination of the active treatment-free survival rate and are informative for making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The authors concluded that although there were differences with respect to active surveillance inclusion, surveillance, and discontinuation criteria between the two cohorts, the risk of deferred active therapy was equally moderate for both groups in the short-term follow-up [19]. Results from two small active surveillance cohorts in Japan [20] and Ireland [21] are in line with published outcomes of established active surveillance cohorts.…”
Section: Published Active Surveillance Short-term Follow-up Outcomessupporting
confidence: 78%
“…The authors concluded that although there were differences with respect to active surveillance inclusion, surveillance, and discontinuation criteria between the two cohorts, the risk of deferred active therapy was equally moderate for both groups in the short-term follow-up [19]. Results from two small active surveillance cohorts in Japan [20] and Ireland [21] are in line with published outcomes of established active surveillance cohorts.…”
Section: Published Active Surveillance Short-term Follow-up Outcomessupporting
confidence: 78%
“…Up to an average of 38% of changes to radical treatments were because of a reclassified Gleason grade (95% CI 27%, 49%, Fig. 4) [14,17,19,[21][22][23]25,27,28,[33][34][35]. In the 17 studies References for the study settings are provided in Table 1.…”
Section: 4mentioning
confidence: 98%
“…detailing reasons, an average of 20% of treatment changes were because of patient choice or anxiety (95% CI 14%, 27%) [12,[14][15][16][17][18][19]22,23,[25][26][27]29,30,32,34,35].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation